2015
DOI: 10.1590/s1516-8913201400152
|View full text |Cite
|
Sign up to set email alerts
|

Torularhodin and Torulene: Bioproduction, Properties and Prospective Applications in Food and Cosmetics - a Review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 47 publications
0
54
0
3
Order By: Relevance
“…Torularhodin is an uncommon carotenoid with potential applications ranging from food technology to pharmaceutics. This carotenoid exhibits strong antioxidant activity, acts as a vitamin A precursor, and has been proposed as a colorant for meat products due to its characteristic red color (Moliné, Libkind, & van Broock, 2012;Zoz, Carvalho, Soccol, Casagrande, & Cardoso, 2015). Recently, the anticancer potential of torularhodin has been demonstrated in vivo on mice (Du et al, 2016).…”
Section: Pigmentsmentioning
confidence: 99%
“…Torularhodin is an uncommon carotenoid with potential applications ranging from food technology to pharmaceutics. This carotenoid exhibits strong antioxidant activity, acts as a vitamin A precursor, and has been proposed as a colorant for meat products due to its characteristic red color (Moliné, Libkind, & van Broock, 2012;Zoz, Carvalho, Soccol, Casagrande, & Cardoso, 2015). Recently, the anticancer potential of torularhodin has been demonstrated in vivo on mice (Du et al, 2016).…”
Section: Pigmentsmentioning
confidence: 99%
“…Zoz et al . () suggested the possible use of TRu and TRo as components of cosmetics and food. Studies of toxicity conducted on rats demonstrated that β‐carotene, TRo and TRu produced by R. glutinis yeasts can be used as innocuous food additives (Latha & Jeevaratanm, ).…”
Section: Resultsmentioning
confidence: 99%
“…The compositions of carotenoids are similar, consisting of β-carotene, γ-carotene, torulene and torularhodin. The torulene is the carotenoid of higher occurrence in yeasts (Zoz et al, 2015).…”
Section: Carotenoids Produced By Yeasts and Filamentous Fungimentioning
confidence: 99%